Cover, Content, and Editorial Note from Borneo J Pharm Vol. 6 No. 3 August 2023 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2023)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published at August 2023. This edition contains ten articles: Pharmacology-Toxicology, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, Microbiology Pharmacy, and Clinical-Community Pharmacy. This edition includes writings from five countries: Cyprus, Indonesia, Malaysia, Nigeria, and the Democratic Republic of the Congo. The authors come from several institutions, including University of Maiduguri, Cyprus International University, Newcastle University Medicine Malaysia, Ahmadu Bello University, Adamawa State Polytechnic, Modibbo Adama University, Politeknik ATI Padang, Universitas Andalas, Politeknik Teknologi Kimia Industri Medan, Université de Kinshasa, Universitas Airlangga, Universitas Ahmad Dahlan, Universitas Islam Negeri Maulana Malik Ibrahim, Universitas Udayana, Institut Teknologi dan Kesehatan Bali, Sekolah Tinggi Farmasi Mahaganesha, and Universitas Gadjah Mada. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on November 2023. Wassalamu’alaikum Wr. Wb.